Sosialisasi Pemanfaatan Lahan Kosong Desa Sukarame Kecamatan Gumay Talang Kabupaten Lahat - Kun Budianto (Jurnal Aksi Dosen dan Mahasiswa, 2024)
This service is carried out with the aim of providing motivation to village communities to utilize empty land owned by residents. This motivation and encouragement to the community is carried out so that they are able to explore their potential and have the courage to act to improve their quality of life by optimizing empty land for cultivating fish ponds and plants that are useful for the community. This service was carried out in Sukarame Gumay Talang Village, Lahat Regency. The method used is the extension method. By carrying out this service, the village community has been motivated to utilize the empty land they own.